Rheumatoid Arthritis – Biological DMARDs 2018
DOI: 10.1136/annrheumdis-2018-eular.1316
|View full text |Cite
|
Sign up to set email alerts
|

AB0456 Efficacy and safety of switching from etanercept reference product to lbec0101 (ETANERCEPT BIOSIMILAR) compared with continuing lbec0101 in patients with rheumatoid arthritis

Abstract: BackgroundLBEC0101 is a newly developed biosimilar of etanercept (ETN). As rheumatoid arthritis (RA) treatment is a long-standing process in the clinical practice, the long-term safety and efficacy of anti-TNF inhibitors have been studied and reported.1 Clinical studies have been conducted to evaluate the efficacy and safety of biosimilar after switching from their originator drug.2 ObjectivesTo evaluate the long-term efficacy, safety, and immunogenicity of switching from the ETN reference product (RP) to LBEC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
(1 reference statement)
0
3
0
Order By: Relevance
“…Switching between biosimilars and bio-originators revealed no changes in efficacy in trials of one ADA (SB5, low RoB),56 three etanercept (two with low RoB: GP2015, LBEC0101; CHS-0214: conference abstract—RoB not assessed),32 57–59 and two infliximab biosimilars (SB2, CT-P13, both low RoB) 60 61. Detailed characteristics and results of the studies are shown in online supplementary tables S2.11 and S3.11.…”
Section: Resultsmentioning
confidence: 99%
“…Switching between biosimilars and bio-originators revealed no changes in efficacy in trials of one ADA (SB5, low RoB),56 three etanercept (two with low RoB: GP2015, LBEC0101; CHS-0214: conference abstract—RoB not assessed),32 57–59 and two infliximab biosimilars (SB2, CT-P13, both low RoB) 60 61. Detailed characteristics and results of the studies are shown in online supplementary tables S2.11 and S3.11.…”
Section: Resultsmentioning
confidence: 99%
“…Five of these consist of a double-blind or open-label RCT of which four were conducted in rheumatology indications. [55][56][57][58] The other study consisted of a multiple switch double-blind RCT (EGALITY) investigating repeated switching between the etanercept RP and GP2015 in patients with plaque psoriasis. 21 Patients were switched at week 12, 18, 24, and 30 and followed up to 52 weeks.…”
Section: Etanerceptmentioning
confidence: 99%
“…There is also a growing body of RCT evidence for adalimumab biosimilars (ABP 501, BI 695501, CHS-1420, FKB 327, GP2017, MSB11022, and SB5) that have, to date, found no impact of switching on efficacy, safety, or immunogenicity [61][62][63][64][65][66][67][68][69]. Switch studies also provide supporting evidence for switching to the infliximab biosimilars SB2 [70], NI-071 [71], and BOW015 [72], along with the etanercept biosimilars GP2015 [73,74], SB4 [75], and LBEC0101 [76], and the rituximab biosimilars CT-P10 [77] and GP2013 [78]. In agreement with previously published systematic reviews, a limitation common to many of the studies included in Table 2 is the lack of adequate statistical power to detect differences between the switched vs continuously treated groups.…”
Section: Switching Studiesrandomized Controlled Trialsmentioning
confidence: 99%